Role of β-Si3N4 seeds in microstructure development and properties of silicon nitride ceramics: a comprehensive review - Govindasamy L.; Park Y.-J.; Ko J.-W.; Lee J.-W.; Ma H.-J.; Kumar K.; Kim H.-N. (My University, 2025)
This review examines the influence of β-Si3N4 seeds on the development of silicon nitride ceramics, a material with exceptional mechanical and thermal properties, making it suitable for a wide range of applications, including automotive, space, and semiconductor industries. As technology advances, there is a growing demand for the development of new silicon nitride ceramic materials superior to the existing ones. The driving force for innovation and development resulted in the examination of β-Si3N4 seeds incorporated silicon nitride system. A self-reinforced microstructure with a bimodal grain size distribution must attain the desired properties, and the incorporation of β-Si3N4 seeds is required to achieve this. Hence, β-Si3N4 seeds are crucial for shaping the microstructure of silicon nitride ceramics and, consequently, their properties. This review article aims to highlight the advancement of β-Si3N4 seeds incorporated silicon nitride systems and its impact on the processing parameters, conditions, chemical composition, microstructure, thermal and mechanical properties. These effects demonstrate the multifaceted benefits of incorporating β-Si3N4 seeds, ultimately leading to improve the overall performance of silicon nitride ceramics. This comprehensive review provides a valuable resource for researchers, offering an insightful exploration of the pivotal role of β-seeds in shaping silicon nitride ceramics, consolidating existing knowledge, and highlighting future research avenues. © The Korean Ceramic Society 2024.